Effects of playing a computer game using a bright display on presleep physiological variables, sleep latency, slow wave sleep and REM sleep - Shigekazu Higuchi; Yutaka Motohashi; Yang Liu; Akira Maeda (2005)
Summary Epidemiological studies have shown that playing a computer game at night delays bedtime and shortens sleeping hours, but the effects on sleep architecture and quality have remained unclear. In the present study, the effects of playing a computer game and using a bright display on nocturnal sleep were examined in a laboratory. Seven male adults (24.7 ± 5.6 years old) played exciting computer games with a bright display (game‐BD) and a dark display (game‐DD) and performed simple tasks with low mental load as a control condition in front of a BD (control‐BD) and DD (control‐DD) between 23:00 and 1:45 hours in randomized order and then went to bed at 2:00 hours and slept until 8:00 hours. Rectal temperature, electroencephalogram (EEG), heart rate and subjective sleepiness were recorded before sleep and a polysomnogram was recorded during sleep. Heart rate was significantly higher after playing games than after the control conditions, and it was also significantly higher after using the BD than after using the DD. Subjective sleepiness and relative theta power of EEG were significantly lower after playing games than after the control conditions. Sleep latency was significantly longer after playing games than after the control conditions. REM sleep was significantly shorter after the playing games than after the control conditions. No significant effects of either computer games or BD were found on slow‐wave sleep. These results suggest that playing an exciting computer game affects sleep latency and REM sleep but that a bright display does not affect sleep variables.